2013
DOI: 10.1007/s12264-013-1374-3
|View full text |Cite
|
Sign up to set email alerts
|

Progressive loss of striatal dopamine terminals in MPTP-induced acute parkinsonism in cynomolgus monkeys using vesicular monoamine transporter type 2 PET imaging ([18F]AV-133)

Abstract: The 1-methyl-4-phenyl-1,2,3,4-tetrahydropyridine (MPTP)-induced parkinsonism model, particularly in non-human primates, remains the gold-standard for studying the pathogenesis and assessing novel therapies for Parkinson's disease. However, whether the loss of dopaminergic neurons in this model is progressive remains controversial, mostly due to the lack of objective in vivo assessment of changes in the integrity of these neurons. In the present study, parkinsonism was induced in cynomolgus monkeys by intraveno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…This increase was statistically significant (p<0.01; Table 3), although the transplanted ANCE neural progenitor cells did not generate dopaminergic neurons, as it was observed that only very few transplanted cells were co-labelled with PKH67 (vital marker of the implanted cells) and TH in a similar MPTP model [26,27]. Several studies have assessed the evolution of the dopaminergic function in MPTP non-human primate models following offset of the MPTP intoxications [30,40,42]. None of them reported such a re-increase of striatal 18F-DOPA uptake after the last MPTP injection.…”
Section: Discussionmentioning
confidence: 99%
“…This increase was statistically significant (p<0.01; Table 3), although the transplanted ANCE neural progenitor cells did not generate dopaminergic neurons, as it was observed that only very few transplanted cells were co-labelled with PKH67 (vital marker of the implanted cells) and TH in a similar MPTP model [26,27]. Several studies have assessed the evolution of the dopaminergic function in MPTP non-human primate models following offset of the MPTP intoxications [30,40,42]. None of them reported such a re-increase of striatal 18F-DOPA uptake after the last MPTP injection.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical rating scale (Kurlan score), which is significantly correlated with the severity of dopaminergic denervation [25,54], was mainly used to evaluate the clinical evolution and outcomes. MPTP was stopped when each animal manifested symptoms typical of clinical PD at different times (mean 11.6 ± 1.52 days), as the Kurlan score increased to *10 (mean 10.4 ± 0.55).…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48][49] Son zamanlarda yapılan aratırmalar, pozitron emisyon tomografisi (PET) görüntülemesine göre, SNPC ve striatumdaki dopa-minerjik nöronal sistemlerin MPTP tedavisi ile zarar gördü¤ünü bildirmitir. [50][51][52] MP T P tedav isindek i ayarlamalar ı hesaplamak için PH semptomlarının bireysel iddetini yansıtan hedef kriterleri belirlemek gereklidir. ‹yi çalımalarda, otomatik video görüntü analiz sistemi, parkinsonian sinomolgus maymununda lokomosyon davranıı için hassas bir objektif ölçüm yöntemi olarak do¤rulanmı ve MPTP tarafından uyarılan PH modelleri için davranısal nicelemeyi ölçmek için kullanılmıtır.…”
Section: Farelerunclassified